Exploring the Deep Ocean Single‐Frequency Microseisms Southwest of Japan in Northern Philippine Sea - Bin Huang; Mei Xue; Zhen Guo; Wenkai Song (Geophysical Research Letters)
Abstract Single‐frequency microseisms (SFMs) have been revealed to be only generated in shallow water for decades, while some recent studies reported them in a deep ocean. Using the continuous waveform data recorded by ocean bottom seismometers, we investigate the deep ocean SFMs in the northern Philippine Sea. Based on the spectrum analysis, we find that the SFMs can be detected in deep ocean and the detection is time variable. To determine the source locations of SFMs, we perform polarization analysis and calculate the cross‐correlation coefficients between SFMs on vertical components and ocean wave energy spectra considering the attenuation of SFMs. Both the polarization and correlation results show that the sources nearby stations dominate the observed Rayleigh‐wave SFMs though distant sources also contribute. Our investigation suggests that the SFMs can be generated in a deep ocean likely by infragravity ocean waves interacting with seafloor topography, which is strengthened by strong ocean storms.